Climate COP-up, COP-out and hyCOPrisy. (1st June 2022) - Clarke, Richard
Abstract : The complexities of climate science, of estimates of global greenhouse gas emissions and of their implications for climate change have not prevented widespread acceptance that global warming is a reality and its consequences potentially catastrophic for our planet and its peoples. But the convoluted processes of international negotiations and the political and economic context of their implementation mean that few have any confidence that national undertakings and international targets will be met. COP26 was a watershed, revealing the lack of progress on the most critical challenge of our time, the hypocrisy and double-speak of capitalist states and corporations, and the co-option of some conservation organisations through a deceptively 'green' narrative. A critical, materialist, Marxist approach can break through the greenwash of official discourse, reveal the need for systemic change, and potentially serve as a focus for growing public awareness and environmental activism.